The internet as the central factor in translation - Twardowski, Marek (2012)
The main objective of this dissertation is to develop a guide for people who set about to carry out a translation. Nowadays, given the multitude of resources available online, translating a text has become much easier – one simply must know how to make the best of these resources. From my experience as a translator, I am aware of how valuable the discovery of a high-quality dictionary, glossary, or other resources can be both in attaining high quality translations and in expediting the processes, especially when it comes to performing a technical translation. I hope my work will help future and present translators in their professional lives.